Effect Of Triamcinolone Trigger Point Injection On Changes In TNF-α Levels And Oswestry Disability Index (ODI) Scores Non-Specific Low Back Pain (LBP) Patients - Mohamad Fakih; Suryadi; Dodik Tugasworo; Dwi Pudjanarko; Amin Husni; Trianggoro Budisulistyo; Arinta Puspitawati (Medica Hospitalia : Journal of Clinical Medicine, 2024)
Background: Low back pain (LBP) is the most common musculoskeletal problem and a major cause of worldwide disability causing increased health costs and indirect costs associated with reduced or lost productivity. One of the therapeutic management of LBP is Triamcinolone trigger point injection. Until now, research on the effect of Triamcinolone trigger point injection on changes in TNF-α levels and Oswestry Disability Index (ODI) scores in Non-Specific LBP patients is still limited. Objective: To analyze the effect of Triamcinolone trigger point injection on changes in TNF-α levels and ODI scores before and after Triamcinolone trigger point injection in Non-Specific LBP patients. Methods: This is a quasi-experimental analytic observational study with a pre and post-test group design approach. Subjects were diagnosed with Non-Specific LBP who had met the inclusion criteria (acute pain less than 3 months, patient age 30-55 years, moderate-severe pain intensity, had never received a Triamcinolone trigger point injection) with the exclusion criteria patients experiencing severe pain. not only caused by NPB. The study subjects were checked for TNF-α levels and ODI scores before and after the Triamcinolone trigger point injection. Then a paired T-test was carried out. Results: During the study period September - November 2022 at the Neurology Outpatient Polyclinic, RSUP Dr. Kariadi Semarang obtained 32 subjects. There was a significant difference between changes in TNF-α levels before and after Triamcinolone trigger point injection (p=0.000). There was a significant difference in ODI scores before and after the Triamcinolone trigger point injection (p=0.000). There was no significant relationship between the risk factors for gender, occupation, BMI, physiotherapy, and changes in TNF-α levels with changes in the ODI score. Conclusion: There is a significant difference in changes in TNF-α levels and ODI scores before and after Triamcinolone trigger point injection.